1995
DOI: 10.1063/1.115181
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dilation by free electrons in heavily doped GaAs:Si

Abstract: Lattice constants of GaAs layers grown by molecular beam epitaxy were examined by using the high resolution x-ray diffractometer. For highly doped samples ͑up to 9ϫ10 18 cm Ϫ3 of free-electron concentration͒ we observed an increase of the lattice constant with respect to the undoped layers. Since substitutional silicon atoms decrease the lattice constant of GaAs, the results are explained by the influence of free-electrons via the deformation potential of the ⌫ minimum of the conduction band. The best fit to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 10 publications
2
19
1
Order By: Relevance
“…It can be seen that the undoped GaSb is unintentionally ptype doped, which is consistent with the results of Anayama et al [10]. When the Be cell temperature is 700 °C, the hole concentration is 7.76×10 16 cm -3 , which is almost the same value as that for undoped GaSb layer (7.43×10 16 cm -3 ), therefore, we can consider that the doping is too weak when the Be cell temperature is 700 °C.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It can be seen that the undoped GaSb is unintentionally ptype doped, which is consistent with the results of Anayama et al [10]. When the Be cell temperature is 700 °C, the hole concentration is 7.76×10 16 cm -3 , which is almost the same value as that for undoped GaSb layer (7.43×10 16 cm -3 ), therefore, we can consider that the doping is too weak when the Be cell temperature is 700 °C.…”
Section: Resultssupporting
confidence: 81%
“…This latter is often used in the MBE growth of III-V materials. Furthermore, it is demonstrated that the presence of dopant atoms in epitaxial atoms changes its electrical and crystallographic properties [9][10][11][12]. It was shown by Sankowska et al that the lattice constant of GaSb layer grown on GaSb substrate decreases by the Be doping and unintentional As dopant.…”
Section: Introductionmentioning
confidence: 99%
“…The 1attice parameters of Semiconduction depend on the following factors: (i) concentrations of dopants or native defects which contract or expand the lattice due to the size effect, (ii) concentration of free charge which changes the lattice parameters via the deformation potential of the extremum occupied by this charge [1][2][3][4][5], (iii) internal and external stresses (for example, due to the presence of a mismatched substrate), (iv) temperature. The latter factor may induce the change of lattice parameters not only by anharmonicity of thermal vibrations, but also by a redistribution of the free charge in the conduction-or the valence-band.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent papers [7][8][9] the experience gained from the studies on Si [1], GaAs [2,3] and AlGaAs [4][5][6] was applied in the explanation of some features of the microstructure of GaN single crystals and epitaxial layers. This material attracts a considerable interest because of the present and future applications in blue-range optoelectronics and high-temperature electronics.…”
Section: Introductionmentioning
confidence: 99%
“…The effects is roughly the same as the lattice expansion by the presence of the free carriers [8][9][10][11]. For n-type of semiconductors the effects is described by the formula where D is the deformation potential, B is the bulk modulus and n is the concentration of electrons.…”
Section: T I O N I S T H E R a T I O O F C O N C E N T R A T I O N O mentioning
confidence: 82%